Efektivitas Self Esteem Dengan Pendekatan Rational Emotive Behavior Therapy (Rebt) Pada Kesehatan Mental Remaja Yatim Di Desa Pulukan, Bali - Amalia, Meila; Sahara, Erlina Rita; Rizqina, Dwi Latifa; Zuhro’ Fitriana, Ani Qotuz (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to investigate the effectiveness of the Rational Emotive Behavior Therapy (REBT) approach in improving the self-esteem and mental health of orphaned adolescents in Pulukan Village, Bali. Orphaned youth often face psychological challenges, including low self-esteem and mental health problems. Therefore, an effective approach is needed to help them overcome this problem. The research methods used in this study are interview and observation methods. The research participants consisted of orphaned youth in Pulukan Village, Bali. This implementation uses the Rational Emotive Behavior Therapy (REBT) approach. First, changing irrational thoughts, second, building self-confidence third, overcoming trauma and sadness fourth, learning healthy coping fifth, improving social relations sixth, increasing self-understanding REBT implementation which must be carried out by a therapist who is trained and has experience in working with children orphan REBT services are carried out in experimental groups over a certain period, with a focus on self-understanding, recognition of irrational thought patterns, and replacement of irrational thought patterns with healthier rational thoughts. After the intervention was completed, both groups were again measured using the same scale to measure changes in self-esteem and mental health. Data analysis in this study, namely content data analysis and thematic data analysis, are two techniques commonly used in qualitative research to analyze data in the form of text, images, audio, or video. The results of this study are expected to provide evidence about the effectiveness of the REBT approach in increasing self-esteem and mental health of orphaned adolescents in Pulukan Village, Bali. If this approach proves to be effective, the implication is the importance of expanding access to REBT-based psychotherapy services for orphaned youth in improving their mental well-being.